Penolakan Pengguna dan Strategi Penyelarasan Aplikasi Sistem Informasi Keuangan dan Akuntansi Dalam Mendukung Penyusunan Laporan Keuangan Koperasi - Kosadi, Ferry (Program Studi Akuntansi FPEB UPI, 2020)
The research objective is to develop the application of financial and accounting information systems (AIS) and optimize the knowledge and capability of the human resources (HR) of savings and loan cooperatives in Bandung with seven branches in Indonesia. True Experimental Method with Pretest-Posttest Experimental Design and Throwaway Prototyping method through a functional business process approach to explore alternative prototypes and find out the user’s resistances so as to get the appropriate alignment strategy solutions. The results are in the form of knowledge and capability gaps in HR and user rejection of computerization, accounting and financial reports. Treatment training and outreach have the effect of increasing the knowledge and ability of computerization, accounting and financial reports. Alignment strategies using Local Area Networks and semi-integrated automation applications Spreadsheets for branches that have not mastered IT and web-based applications at other branches with the head office as the central process of accounting and financial reports. The commitment of the Management and special staff in the organizational structure as maintaining the infrastructure, securing the database, empowering and mentoring for HR is an important part in the process of adapting to improving and accelerating behavior change and business processes of IT-based cooperative businesses.Abstrak.Tujuan penelitian mengembangkan aplikasi sistem informasi keuangan dan akuntansi (SIA) dan mengoptimalkan pengetahuan dan kemampuan sumber daya manusia (SDM) koperasi simpan pinjam di Bandung dengan tujuh cabang di Indonesia. Metode True Experimental dengan Pretest-Posttest Experimental Design dan metode Throwaway Prototyping melalui pendekatan proses bisnis fungsional untuk mengeksplorasi alternatif prototype dan mengetahui penolakan pengguna sehingga mendapatkan solusi strategi penyelarasan yang sesuai. Hasil berupa kesenjangan pengetahuan dan kemampuan SDM serta penolakan pengguna pada komputerisasi, akuntansi dan laporan keuangan. Treatment pelatihan dan sosialisasi memberikan dampak peningkatan pengetahuan dan kemampuan komputerisasi, akuntansi dan laporan keuangan. Strategi penyelarasan menggunakan Local Area Network dan aplikasi semi terintegrasi otomatisasi Spreadsheet untuk cabang yang belum menguasi TI dan aplikasi web based pada cabang lainnya dengan kantor pusat sebagai sentral proses akuntansi dan laporan keuangan. Komitmen Manajemn dan staf khusus dalam struktur organisasi sebagai pemelihara infrastruktur, pengamanan database, pemberdaya dan mentor bagi SDM menjadi bagian penting dalam proses adaptasi peningkatan dan percepatan perubahan perilaku dan proses bisnis koperasi berbasis TI.